(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
This article follows a final degree for the Bachelor of Social Work and intends to analyze and reflect on the experiences of women in prostitution in 2015 in the city of Santa Rosa, in light of the abolitionist paradigms and/ or regulationist. In this way it seeks to understand the meanings attributed women to practice prostitution and relationships that occur in it.